2019
DOI: 10.1027/1618-3169/a000457
|View full text |Cite
|
Sign up to set email alerts
|

Bald and Bad?

Abstract: Abstract. According to (a) the beauty ideal of a full head of hair and (b) the physical attractiveness stereotype (PAS; “what is beautiful is good”), bald men should appear less attractive than nonbald men, not only physically but also socially. To explain inconsistent results on this prediction in previous research, we suggest two antagonistic processes: the automatic activation of the PAS at the implicit level and its suppression at the explicit level, the latter process selectively triggered by individuatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 81 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…We feel these findings are still notable; however, as men were only exposed to five images each and were only asked a single and specific question about facial expressions (i.e., instead of vague and/or multiple questions that could have influenced responses to baldness). These findings complement previous research that has also shown bald men to be negatively stereotyped relative to their non-bald counterparts [41][42][43][44] even when it comes to interpreting their facial expressions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We feel these findings are still notable; however, as men were only exposed to five images each and were only asked a single and specific question about facial expressions (i.e., instead of vague and/or multiple questions that could have influenced responses to baldness). These findings complement previous research that has also shown bald men to be negatively stereotyped relative to their non-bald counterparts [41][42][43][44] even when it comes to interpreting their facial expressions.…”
Section: Discussionsupporting
confidence: 88%
“…Such studies have typically found that men with baldness are rated as less attractive, unsuccessful and older. [41][42][43][44] Although some studies offer conflicting findings showing neutral or even positive connotations with baldness (including increased perceived intelligence and honesty). 41,45 For example, Mannes 44 found that participants rated bald men as more dominant, taller, muscular, older and less attractive than men with full heads of hair.…”
Section: Baldness Dissatisfaction and Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…In general, when visible physical changes impact psychological and physical well-being, leading to impaired QoL, cosmetics may have a restoring effect on QoL (Ferreira et al, 2016;Rudolph et al, 2019). Male hair loss increases exponentially between the ages of 30 and 40 years (Budd et al, 2000), having a significant effect on QoL (Kranz et al, 2019). Face moisturizer, frequently used by women and men from all age groups, has been reported as appealing because skin is the most noticeable sign of aging, and health and appearance are a fundamental part of overall well-being (Buranasirin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Theme 3 demonstrated resistance on the forums to the notions that baldness was distressing and/or stigmatised. Researchers have found 35,36 that those who are balding can and do develop alternative and more positive perspectives on baldness (including by comparing baldness to terminal medical conditions). Indeed Kranz 12 found that men who accepted their baldness were significantly less distressed than men who attempted to compensate or "reverse" their baldness, and that this was the case regardless of age, especially if baldness was more significant.The findings are particularly pivotal when considered in the broader socio-cultural context, where the idea that baldness must be devastating is widespread and extensively promoted through the process of "commercial medicalisation."…”
Section: Resistance To Baldness Despairmentioning
confidence: 99%